Governance of uncertainty in implementing mobility innovations: A comparison of two Dutch cases. (May 2023) - Akse, Ruben; Veeneman, Wijnand; Marchau, Vincent; Ritter, Simone
Abstract: To make the supply of transport services more attractive and sustainable, mobility suppliers and governmental actors expect much from mobility innovations. When developing and realizing these innovations, they experience considerable uncertainty about the future outcomes of implementing these innovations (1), and about other actors' intentions and actions in realizing these innovations (2). Literature on governance under uncertainty often overlooks the experienced uncertainty during interactions among multiple actors. To address this gap, this paper applies a new conceptual model for understanding interacting actor behaviour under uncertainty in the context of two innovative mobility cases in the Netherlands: Mobility as a Service (a digital channel for users to plan, book, and pay for multiple mobility services) and ERTMS (a new European rail traffic control system). Our analysis reveals that actors tend to rely on traditional project management approaches for dealing with uncertainty, even when there is no shared understanding of innovation requirements and scope. However, uncertainty manifests itself most regarding actors' intentions and actions in the development phase of innovations. This gap underscores the limitations of managing innovations using project management and highlights the need for additional governance approaches to address the major uncertainties that actors face about their mutual relations.